Widowhood Woes: The Bayelsa Experience - Uche, Rachel D. (Advances in Social Sciences Research Journal, 2015)
The death of a husband is traumatic enough, yet the plight of the widow oftentimes, is further compounded by society and its traditions. The study, therefore, sought to determine the extent of adjustment among widows in Bayelsa State. The ex-post facto design was used and a sample size of 200 was derived through probability sampling technique. Two hypotheses were formulated and data collected using questionnaire which was analysed using Independent t-test. Results revealed that widowhood adjustment significantly differed on the bases of (1) Spirituality and (2) Age. It was concluded that adjustment tend to be easier for widows of higher spiritual level and those who are older. It was recommended for counsellors to be aware of the spiritual and other issues in their widow-clients lives and assist them to capitalize on these areas of strengths.